Global fishing between jurisdictions with unequal fisheries management. (1st November 2022) - Klein, Carissa J; Kuempel, Caitlin D; Watson, Reg A; Teneva, Lida; Coll, Marta; Mora, Camilo
Abstract: The demand for seafood is increasing globally and is being met, in some cases, by unsustainable fishing practices. When a country fishes outside of its jurisdiction, any negative social and environmental impacts associated with fishing are displaced to the fished location and may not be compensated. This is particularly problematic when a country fishes in jurisdictions with poorer, less-effective, fisheries management than itself (henceforth 'unequal displacement'). Using two different indices for national fisheries management effectiveness, we calculated unequal displacement of wild-capture seafood globally. We found that up to 23% (19.8 Mt) of seafood was unequally displaced annually between 1976–2015, most of which was caught in the high seas. During the period that the management effectiveness data is most accurate (2007–2011), almost all 172 countries unequally displace seafood ( n = 123), but a few are responsible for the majority (China, India, Japan, Norway, Russia, Republic of Korea, Spain, Taiwan, Thailand). Achieving both sustainable food provision and ocean health requires improving international fishing and trade policies targeted at these countries to encourage the reduction of unequal seafood displacement.